Editorial: Public health and public wealth – an introduction. (27th August 2010) - Haynes, Michael
In recent decades, there has been a growing shift towards the use of markets and quasi-markets in healthcare provision and an increasing managerialism in the context of major increases in expenditure. The paper offers some comparative data on these trends and poses some basic questions as to whose interests have been served by this and whether this has been the best way to improve patient provision and health outcomes.